Synthesis, characterization, enhanced sunlight photocatalytic properties, and stability of Ag/Ag3PO4 nanostructure-sensitized BiPO41. Issue 54 (13th June 2015) - Huang, Tzu-Yun; Chen, Yen-Jui; Lai, Chi-Yung; Lin, Yang-Wei
<x xml:space="preserve">Abstract</x> Sunlight-induced photocatalytic activity using Ag/Ag3PO4/BiPO4.